Hans Werner Sinn and Timo Wollmershaeuser’s Target Loans, Current Account Balances and Capital Flows: The ECB’s Rescue Faciliy. A Comment - SCHILIRÒ, Daniele (Journal of Advanced Research in Law and Economics; Vol 4 No 1 (2013): JARLE Volume IV Issue 1(7) Summer 2013, 2016)
The present paper firstly examines and comments the arguments proposed by Werner Sinn and Wollmershaeuser in their paper: ‘Target loans, current account balances and capital flows: the ECB’s rescue facility’. Secondly, this contribution suggests an alternative view for solving the crisis in the eurozone adopting a coopetitive strategy and also regarding the role of the European Central Bank.
Keywords: target loans, current account balances, capital flow, ECB’ rescue facilities, ECB’s role, coopetition